CONSTITUTIONAL IDENTITY AND INTEGRATION – THE RELATIONSHIP OF THE MEMBER STATES AND THE - Elbek Khasanov (Modern American Journals, 2026)
In the process of European integration, the reference to the Community building has long been the main theme, and the Member States have adopted it in the name of the benefits they will derive from the creation of a supranational entity. However, the identities of individual Member States were not lost in this construction of a “Community of States”, because the movement from all sides was in the direction of a European supranational body in which members could recognize themselves mutually and peacefully. Recent cases happened between the EU and Member States' governments triggered the question how constitutional identity of the supranational body is important to review in respect of Member States' legislation and their national identities.
Keywords: Constitutional identity, national identity, sovereignty of the EU, EU legislation